Peran Financial Technology (Fintech) Syariah dalam Perekonomian Negara di Indonesia - Rozi, Fahrur; Safitri AR, Sri Wahyuni; Khowatim, Khusnul; Rochayatun, Sulis (ITB AAS INDONESIA Surakarta, 2024)
This study discusses Financial Technology (Fintech) emerging as a significant innovation offering financial services through digital platforms. The aim of this research is to provide an overview and paradigm of Shariah Fintech and its development in Indonesia, and to depict the role of Shariah Financial Technology (Fintech) in the country's economy. The research method employed is Library Research, where various literature sources such as books, journals, and research reports are deeply studied. The research findings indicate that Shariah Fintech in Indonesia plays a crucial role in the country's economy. They not only provide financial solutions in accordance with Shariah principles but also open up financial access for UMKM. Its growth promises to enhance financial inclusion and support UMKM in Indonesia. However, there are still challenges such as limited infrastructure, lack of human resources, and regulatory constraints in Indonesia. Overcoming these challenges requires cooperation among the government, regulators, industry players, and society in Indonesia. Thus, Shariah Fintech in Indonesia can continue to contribute to the country's economy.